AKTIVITAS DEGRADASI SAMPAH ORGANIK DALAM BIOPORI - Sri Wiedarti; M. Akhmar Yusfi Lubis; Oom Komala (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2015)
Biopori is pore space or in the ground formed by living creatures, such as microorganisms of the soil and plant roots. The shape resembles biopori hole in the ground and forked branches and very effective to channel water and air into the soil. In order to make the hole biopori still function optimally it should be routine coupled with organic material, so in the hole biopori absorption will still take place in aerobic composting process by soil microorganisms.The addition of microbes in accelerating the process of degradation of the garbage that is by adding a inoculum composite comprising four microorganism Saccharomyces, Â Lactobacillus, Acetobacter sp., and Bacillus. The addition of the best treatment with the addition of inoculum and soil, have physical characteristics that resemble the physical characteristics of the soil.Â Key words: Biopori, organic waste, microbes